Phonetic Context and Nasalance Score in Word Level - Leila Ghelichi; Younes Amiri-Shoki; Mohammad Sadegh Jenabi; Bijan Khorasani (University of Social Welfare and Rehabilitation Sciences, 2005)
Objective: Evaluation of nasalance is one of the important factors of instrumental evaluation of voice in persons susceptible to resonance disorder. There are different factors which can affect nasalance score. One of the most important factors is phonetic context of words and the other is sentences. We studied some effects of this important factor on nasalance score in normal Farsi speakers. Materials & Methods: This study is a cross-sectional and descriptive-analytic study of nasalance scores of words in 62 male and 60 female normal and Farsi speakers aged 18-27 years old. Subjects were selected from students of rehabilitation college which hadn't any auditory, articulatory, fluency, and resonance problem. They hadn't cold, or any other disease which could affect their voice. Twelve printed words (6 words with and 6 words without nasal consonants) were read by each of subjects, and nasalance of them were calculated by Nasal View, and then, the gathered data were analysed. Results: Mean Nasalance scores of words without nasal consonants in ascending order are for words /dâd/, /bâl/, /dærd/, /bur/, /did/, and /bil/ SDs are nearly follow this order. Mean Nasalance scores of words with nasal consonants in ascending order are for words /mâl/, /nærd/, /dân/, /mur/, /mil/, and /din/ SDs are nearly follow this order. Maximum nasalance score in nasal words is for /din/, and minimum is for /mâl/. Maximum nasalance score in nonnasal words is for /bil/, and minimum is for /dâd/. Mean nasalance scores of males and females are compared with each other. Conclusion: Findings of this study prepared useful information about nasalance score in adult Farsi speakers wich can be a good start for access to standardized data for different aspects of voice. In addition, it shows that mean nasalance score of words can be significantly changed with these factors: different vowels, presence or absence of nasal consonants, and gender. This study shows the necessity of investigating about the effect of different phonetic contexts, manner and placement of articulation too.